Impact of Bioactive Peptides on Human Health - Kaustav Majumder (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Food-derived bioactive peptides or dietary peptides are increasingly becoming recognized as major food compounds for human health promotion, which prevent the occurrence of chronic diseases through their impacts on the gastrointestinal, cardiovascular, immune, and nervous systems. Further bioactive peptide discoveries are essential for maintaining human health and commercial development in the area of functional foods and nutraceuticals. This Special Issue covers a wide range of research topics specifically on food-derived bioactive proteins and peptides including the in-vitro and in-vivo evaluation of biological activities, bio-accessibility, intestinal absorption, bioavailability, the effect on chronic diseases, and the modulation of human nutrition.